The Teaching Method of Graphic Design in Brazil, Methodology of Brand Development and Their Market Outcomes - Ricco Placido da Silva, Joao Carlos [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Placido da Silva, Jose Carlos [UNESP]; Stephanidis, C. (Springer, 2015)
The growth of the number of graphic designs to meet the needs of the market has reduced the development process of the same, making them incomprehensible. The use of a suitable method enables new professionals to develop more functional designs. This study lists the problems encountered on the market, using interviews in empreses, and directing the teaching of projetual method in Brazilian schools, focusing on graphic design brands. With that can identify possible improvements in this field.
Keywords: Education; Graphic marks; Projective methods